Hubungan Dukungan Keluarga dengan Loneliness pada Lansia di Desa Binjeita Kecamatan Bolangitang Timur - Bayu Dwisetyo; I Made Rantiasa; Gymnastiar Sanggilalung (Universitas Muhammadiyah Manado, 2024)
Good quality family support can help reduce feelings of loneliness and improve one's emotional well-being. Conversely, a lack of support or poor family relationships can exacerbate feelings of loneliness. When compared to other problems, loneliness is a major cause of stress. This study aims to determine the relationship between family support and loneliness in the elderly in Binjeita village, East Bolangitang District. This study used descriptive analytic method with cross-sectional approach. Respondents were 52 using the porpusive sampling method. Data collection between the two variables was carried out using a family support questionnaire and UCLA loneliness scale version 3 based on inclusion and exclusion criteria. The collected data were analyzed using the chi-square. The results of this study were 40 respondents (76.9%) who had good family support and 42 respondents (80.0%) were not loneliness with 20 men and 32 women. The results of the chi square test with a p value = 0.000, with a p value smaller than alpha (α) = 0.05.In conclusion, there is a significant relationship between family support and loneliness in the elderly in Binjeita Village, East Bolangitang District. Suggestions for families in Binjeita Village, East Bolangitang District can provide support to the elderly to reduce loneliness.